2002
DOI: 10.1101/gr.196802
|View full text |Cite
|
Sign up to set email alerts
|

Metallochaperones and Metal-Transporting ATPases: A Comparative Analysis of Sequences and Structures

Abstract: A comparative structural genomic analysis of a new class of metal-trafficking proteins can provide insights into the intracellular chemistry of reactive cofactors such as copper and zinc. Starting from the sequences of the metallochaperone Atx1 and from the first soluble domain of the copper-transporting ATPase Ccc2, both from yeast, a search on the available genomes was performed using a homology criterion and a metal-binding motif xЈ-xЉ-C-xٞ-x٣-C. By limiting ourselves to 20% identity with any of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
345
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 260 publications
(357 citation statements)
references
References 89 publications
4
345
0
8
Order By: Relevance
“…4; see also the supporting information). The three negatively charged residues of Ccc2a are conserved in WLN4, but only two are conserved in WLN2, WLN5, and WLN6 (16). As HAH1 interacts with WLN4 and WLN2 but not with WLN5-6, we may conclude that electrostatic charges are important but not unique factors in the protein-protein interactions.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…4; see also the supporting information). The three negatively charged residues of Ccc2a are conserved in WLN4, but only two are conserved in WLN2, WLN5, and WLN6 (16). As HAH1 interacts with WLN4 and WLN2 but not with WLN5-6, we may conclude that electrostatic charges are important but not unique factors in the protein-protein interactions.…”
Section: Resultsmentioning
confidence: 88%
“…The longest linker between WLN4 and WLN5 provides natural separation of N-WLNP into two parts: WLN1-4 and WLN5-6. Such a feature is not found in the bacterial and yeast copper-transporting ATPases, which have only one or two metal-binding domains (16). This topological organization suggests that the two parts can be treated independently from a structural point of view and that the different linker lengths connecting these domains is likely to be important for copper trafficking and regulation of WLNP in response to copper binding.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…1A). Structural work has demonstrated that Cu chaperones and target metal-binding domains from various organisms possess the same fold and coordinate the metal via two surfaceexposed cysteines in the MXCXXC motif (13)(14)(15)(16)(17)(18)(19)(20)(21). Although the methionine in the first position of the MXCXXC motif is conserved in all organisms, it is not directly involved in metal ligation (13).…”
mentioning
confidence: 99%
“…Human Atox1 is a 68-residue protein that, like the metalbinding domains in ATP7A and ATP7B, has a ferredoxin-like ␣/␤-fold and a single MXCXXC copper-binding motif (12,13) (Fig. 1A).…”
mentioning
confidence: 99%